Inflation as Redistribution. Creditors, Workers, Policymakers - Shimshon Bichler; Jonathan Nitzan (Capital as Power - Toward a New Cosmology of Capitalism, 2023)
This paper is part of a dialogue with Blair Fix on how inflation redistributes income between creditors and workers and the way in which monetary policy affects this process. In his 2023 paper, `Inflation! The Battle Between Creditors and Workers', Fix shows, first, that the impact of U.S. inflation on creditor-worker distribution has been historically contingent (favouring workers during some periods and creditors in others); and second, that since the 1970s, Fed policy to combat inflation with higher interest rates boosted the yield of creditors relative to the wage rate of workers. Our own research suggests that these conclusions might be too general. We point out that creditors are not a monolithic class and that different types of creditors are affected differently, and often inversely, by the rate of interest. We illustrate that, contrary to bank depositors, bondholders tend to lose from inflation. And we show that monetary policy, at least in the United States, appears to follow rather than determine market yields. More generally, since most capitalists nowadays are lenders as well as borrowers, and given that `dominant capital' profits from the full spectrum of investment instruments, we wonder if `creditors' is still a useful category for analysing redistribution in general and inflationary redistribution in particular.
Keywords: G12; E5; J3; D3; E5; 330; Blair Fix; bond yields; creditors; income distribution; inflation; interest rate; monetary policy; total returns; wages